Zinc phthalocyanine/carbon nitride as photocatalyst for removal of aniline - Eliza, Tan Kai Ing, 1990-; Leny Yuliati, supervisor; Fakulti Sains (2014)
Project Paper Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2014